Policy deviations, uncertainty, and the European Court of Justice - Carsten Hefeker; Michael Neugart (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
The implementation of European Union directives into national law is at the discretion of member states. We analyze incentives for member states to deviate from these directives when the European Commission may sue a defecting member state and rulings at the European Court of Justice (ECJ) are uncertain. We find that higher uncertainty about the preferences of the ECJ increases policy deviation, irrespective of whether a case is taken to court or not. If decisions of member states to deviate are interdependent, the incidence of field cases decreases while for those policies reaching the ECJ deviations increase.
Keywords: D72; D78; K41; 330; European Union law; directives; compliance; European Court of Justice; court behavior; uncertainty; legal process; European Commission